Legal Effects of the Ratification of the Job Creation Law on the Existence of Psychics and Shamans as Medical Personnel - Yustisia, Andaru Puspa (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2023)
Law Number 11 of 2020 is an Omnibus law, namely by simplifying amendments or even revoking a number of regulations and laws that were previously in force in order to harmonize existing rules, and codified simply in one law, namely the Job Creation Law. In this case, it will be raised regarding the juridical implications of the ratification of the Job Creation Law on the existence of psychics and traditional healers as medical workers. The research method used in this research is the use of a normative juridical approach and the data used as a data source in this research is secondary data through literature study. The inclusion of psychics as medical personnel in the omnibus law has sparked controversy in the community because the recognition of psychics in the law by the state in this context is considered to equalize professional medical personnel such as doctors with psychics. In addition to paranormals, the community also focused on the inclusion of traditional birth attendants as providers of medical health services. In the omnibus law, TBAs are listed along with midwifery, which has drawn cons, especially from midwives themselves.